KOMPOSISI HASIL TANGKAPAN BAGAN APUNG DI PERAIRAN TANJUNG VADSIT, KABUPATEN MALUKU TENGGARA - Anwar, Yanto; Hukubun, Wiwien G.; Yamlean, Yuda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Lift nets are a common fishing gear used in small-scale fisheries in coastal areas of Indonesia, including in Southeast Maluku Regency. This study aims to analyze the composition of floating lift net catches, variations in catches between fishing trips, and the condition of aquatic environmental parameters in Tanjung Vadsit, Southeast Maluku Regency. The study was conducted in October 2024 using direct observation methods during ten fishing trips. Data collected included the type and weight of catches and aquatic environmental parameters such as temperature, salinity, pH, and current velocity. Data analysis was conducted using descriptive quantitative methods. The results showed that the composition of floating lift net catches was dominated by small pelagic fish, especially anchovies (Stolephorus indicus), scad (Sardinella fimbriata), and blue anchovies (Engraulis encrasicolus). The total catch showed variations between fishing trips, reflecting the dynamics of fish resource availability and aquatic environmental conditions. Aquatic environmental parameters during the study were in a relatively stable range and supported fishing activities using floating lift nets. The results of this study are expected to provide basic information to support the sustainable management of floating net fisheries in the coastal areas of Southeast Maluku.Keywords: lift net, catch composition, small pelagic fish, capture fisheries